Epitope mapping using immunopeptidomics reveals novel immunodominant CD8 T cell epitopes of the AAV9 capsid - Balasubramanian, Akhila; Prachar, Marek; Klaproth, Birgit; Copeland, Victoria; Justesen, Sune; Wen, Yi; Siegel, Robert W.; Malherbe, Laurent P. (Frontiers in Immunology, 2025)
IntroductionAdeno-associated virus (AAV)-mediated gene therapy is a promising approach to treat genetic disorders, offering advantages such as high transduction efficiency, diverse tissue tropism, and an acceptable safety profile. However, the immunogenicity of AAV vectors, particularly the activation of AAV capsid-specific CD8 T cells, significantly impacts therapeutic efficacy and safety. Capsid-specific T cell responses are currently monitored in the clinic using overlapping peptides, which do not represent the naturally presented capsid immunopeptidome. Our previous work identified the naturally presented peptides of AAV capsids using MHC-associated peptide proteomics (MAPPs).MethodsIn this study, we compared overlapping and MAPPs-derived peptides of the AAV9 capsid in their capacity to trigger capsid-specific T cell responses in healthy donor PBMCs.ResultsBoth peptide groups induced measurable T cell responses in FluoroSpot assays only after an expansion phase, reflecting the low frequency of circulating capsid-specific T cells in both seropositive and seronegative donors. Surprisingly, overlapping and MAPPs-derived capsid peptides expanded largely distinct T cells that did not cross-react. The T cell response to MAPPs-derived capsid peptides was dominated by capsid-specific CD8 T cells recognizing peptides eluted from HLA Class I, allowing us to identify CD8 T cell capsid epitopes in healthy donors. By screening 13 matrix pools (comprising 41 HLA Class I MAPPs peptides of the AAV9 capsid) in 24 healthy donors using FluoroSpot assays, we identified ten epitopes eliciting IFN-γ release in at least one donor. 9 of the 10 identified epitopes were novel, varied between 9–13 amino acids in length, and displayed strong binding to their predicted HLA binding alleles. Only one of four previously reported capsid CD8 T cell epitopes elicited a response in the tested cohort of healthy donors with diverse HLAs. Remarkably, in two instances where MAPPs peptides of different lengths were presented on HLA Class I, CD8 T cell response was only observed to longer epitopes.DiscussionOur results represent the first extensive analysis of the naturally presented peptides of the AAV9 capsid. This work provides strategies to improve the detection of the capsid-specific CD8 T cell response in the clinic and reduce vector immunogenicity through the identification of novel CD8 T cell epitopes.